2007
DOI: 10.1111/j.2007.0018-0661.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis for earliness characters in line×tester population of Gossypium hirsutum L.

Abstract: The objective of this study was to estimate the general combining ability of the parents and specific combining ability of hybrids for earliness traits for line selection. Inheritance and interrelationships of earliness characters were evaluated in a line x tester design. Three intermediate-early-maturing female (lines) which are grown regionally and four early-maturing males (testers) cotton varieties were crossed in 2003. The twelve F(1) and seven parents were planted randomized block design with three repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 14 publications
10
32
0
2
Order By: Relevance
“…Significant differences were detected among parents and hybrids in both fiber quality parameters and the line × tester analysis method has been widely used in self-and cross-pollinated plants by plant breeders (Konak et al, 1999;Mert et al, 2003;Ahuja and Dhayal, 2007;Basbag et al, 2007). Sprague and Tatum (1942) used the term "general combining ability" (GCA) to designate the average performance of a line in hybrid combinations, and they used the term "specific combining ability" (SCA) to define those cases in which certain combinations perform relatively better or worse than expected on the basis of the average performance of the lines involved.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences were detected among parents and hybrids in both fiber quality parameters and the line × tester analysis method has been widely used in self-and cross-pollinated plants by plant breeders (Konak et al, 1999;Mert et al, 2003;Ahuja and Dhayal, 2007;Basbag et al, 2007). Sprague and Tatum (1942) used the term "general combining ability" (GCA) to designate the average performance of a line in hybrid combinations, and they used the term "specific combining ability" (SCA) to define those cases in which certain combinations perform relatively better or worse than expected on the basis of the average performance of the lines involved.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different breeding tools, the line × tester analysis is used in both self as well as cross-pollinated crops to estimate general and specific combining abilities of specific traits and to determine favourable parents and crosses (Kempthorne, 1957). Combining ability analysis is an important tool for the selection of desirable parents together with the information regarding nature and magnitude of gene effects controlling quantitative traits (Basbag et al, 2007). Assessment of combining ability has been undertaken in some legume crops such as soybean (Mebrahtu and Devine, 2009); pigeonpea (Singh and Singh, 2009); pea (Narayan et al, 1998;Dhillon et al, 2006;Singh et al, 2007;Sharma et al, 2007;Ceyhan, 2003;Ceyhan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of plant development, earliness may be described in reference to budding date, flowering timing (FT) and the whole growth period (WGP) [4]. Other agronomic traits, such as plant height (PH), node of the first fruiting branch (NFFB) and height of the NFFB (HNFFB), have also been used as earliness indexes [5, 6]. For example, Godoy and Palomo concluded that the lower the NFFB and the shorter the PH, the earlier the maturity [5].…”
Section: Introductionmentioning
confidence: 99%